Targeted Plasmalogen Supplementation: Effects on Blood Plasmalogens, Oxidative Stress Biomarkers, Cognition, and Mobility in Cognitively Impaired Persons - Goodenowe, Dayan B.; Haroon, Jonathan; Kling, Mitchel A.; Zielinski, Margaret; Mahdavi, Kennedy; Habelhah, Barshen; Shtilkind, Leah; Jordan, Sheldon (Frontiers in Cell and Developmental Biology, 2022)
Plasmalogens are a specific type of glycerophospholipid found in especially high levels in neuronal membranes. Decreased blood and brain levels of docosahexaenoic acid (DHA) containing plasmalogens are associated with decreased cognition and neuromuscular function in humans. Administration of 1-O-alkyl-2-acylglycerol (AAG) plasmalogen precursors containing DHA at the sn-2 position dose-dependently increase blood DHA plasmalogens and are neuroprotective in animal models of neurodegeneration at doses between 10 and 50 mg/kg. We conducted an investigational clinical trial in 22 cognitively impaired persons to evaluate the effects of an escalating oral dosing regimen of DHA-AAG from 900-3600 mg/day over a 4-month period on blood serum plasmalogen and non-plasmalogen phospholipids and oxidative stress biomarkers. Safety, tolerability and therapeutic effects on cognition and mobility were also evaluated. DHA plasmalogen levels increased with increasing dose and remained significantly elevated at all treatment doses and durations. DHA plasmalogen levels were positively associated with catalase activity and negatively associated with malondialdehyde (MDA) levels. DHA-AAG supplementation normalized catalase activity in persons with low baseline catalase activity, normalized MDA levels in persons with high baseline MDA levels, and normalized superoxide dismutase activity in persons with high baseline SOD activity. Cognition improved in nine participants, was unchanged in nine, and declined in four. Mobility improved in twelve, was unchanged in five and declined in four participants. Changes in cognition and mobility were statistically significant versus a random outcome. Baseline DHA-plasmalogen levels were not predictive of clinical response. DHA-AAG was well tolerated at all dosages and no adverse reactions were observed.